The Legal Regime of Internship in Romania in terms of the Regulation Contained in Law No. 176/2018 of the Internship with Subsequent Completions and its Relevance for Business Environment - Radu-Ștefan PĂTRU (Communications of International Proceedings, 2021)
In the present study, the author, starting from the premiere regulation of the internship in Romania, analyzes the provisions of Law no. 176/2018 regarding the internship and the legislative act that completes the mentioned law, respectively the Government Emergency Ordinance no. 13/2019. The internship activity has acquired its own regulation, the legislator providing the necessary legal framework for an essential stage in the life of future professionals, namely the quality of intern at a host organization, which ensures, among other things, the transition from education to labor market. The internship will also be analyzed in terms of its importance from the perspective of entrepreneurs, inevitably interested in attracting young staff in order to form a professionally successful team. The content elements that circumstance the internship activity in Romania will be presented with emphasis on the internship contract, which represents the legal foundation of the internship.
Keywords: Internship; First Regulation in Romanian Legislation; Contract; Intern; Host Organization